Image of Confrontation in Modern Cinematic Practices about the Space Race - K. O. Dobronravov (Дискурс, 2025)
Introduction. The space race plays an important role in shaping the modern narrative, justifying political ambitions, technological progress, and the status quo. Therefore, the aim of the article is to analyze the image of confrontation between two superpowers during the space race.Methodology and sources. The article uses a comparative analysis of various narrative models and visual imagery in domestic and foreign movies. An interdisciplinary approach is applied to understand the specificities of the formation of the image of confrontation. The main sources of the research are the works of theorists in memory studies such as P. Hutton, Jan Assmann, M. Halbwachs, P. Nora, as well as contemporary researchers of Russian cinema O.J. Malinova, E.А. Piskunova, D.V. Medyanets, N.A. Lysova, E.A. Perova, as well as the concept of mimetic desire by R. Girard.Results and discussion. It has been shown that modern Russian movies dedicated to space exploration construct an image of timeless confrontation between Russia and the West. This narrative permeates the imperial and Soviet past, and is also reflected in contemporary political rhetoric. The plot is based on the idea of mimetic rivalry between two superpowers. The motivation of the characters in domestic and foreign films intersects. However, while the domestic narrative appeals to nostalgia for the past, the foreign one is built on opposition to the past on issues of gender, racial, and national discrimination.Conclusion. The conclusion is drawn about the dominant role of past achievements in constructing collective memory. Heroism is demonstrated through the mobilization of internal resources in “peaceful” times and humanization of previously mythologized heroic images.